2007
DOI: 10.1158/1078-0432.ccr-07-0499
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Adenovirus-Mediated Delivery of Herpes Simplex Virus Thymidine Kinase Administration Improves Outcome of Liver Transplantation in Patients with Advanced Hepatocellular Carcinoma

Abstract: Purpose: Previous poor results of liver transplantation (LT) have been confirmed in patients with advanced hepatocellular carcinoma (HCC). Adenovirus-mediated delivery of herpes simplex virus thymidine kinase (ADV-TK) therapy is an established adjuvant treatment in cancer, and we evaluated its potential as an adjuvant treatment for HCC patients who underwent LT.Experimental Design: Forty-five HCC patients with tumors >5 cm in diameter participated in the study over a follow-up period of 50 months. Among these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 34 publications
0
50
0
1
Order By: Relevance
“…TP53 gene therapy, particularly adenovirus-mediated rAd-P53 gene therapy, has been used for the clinical treatment of head and neck squamous cell carcinoma, with good clinical outcomes, determined by increased survival times (27,28). The arterial infusion approach can ensure that large amounts of the high-concentration drug can access to tumor cells, with only small amounts of the drug entering the circulation, thus maximizing the therapeutic efficacy and reducing the systemic adverse effects (29). Further laboratory tests showed that there were no significant side effects following adenovirus-mediated rAd-p53 gene therapy by the arterial infusion approach in terms of hematological profiles, and liver and kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 gene therapy, particularly adenovirus-mediated rAd-P53 gene therapy, has been used for the clinical treatment of head and neck squamous cell carcinoma, with good clinical outcomes, determined by increased survival times (27,28). The arterial infusion approach can ensure that large amounts of the high-concentration drug can access to tumor cells, with only small amounts of the drug entering the circulation, thus maximizing the therapeutic efficacy and reducing the systemic adverse effects (29). Further laboratory tests showed that there were no significant side effects following adenovirus-mediated rAd-p53 gene therapy by the arterial infusion approach in terms of hematological profiles, and liver and kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…This is congruent with the results observed in other clinical studies that had employed Ad.TK/GCV for the treatment of different cancers such as ovarian, prostate, mesothelioma, glioma and metastatic colorectal carcinoma. 11 The experience using Ad.TK/GCV in patients with advanced HCC is scarce, 30 and for secondary liver tumors the results from a single clinical trial in patients with metastatic colorectal carcinoma have been published. 31 In the latter, authors demonstrated the safety of direct injection of up to 10 13 vp of an adenovirus coding for TK into metastatic colorectal liver tumors followed by GCV treatment; nevertheless no objective antitumor responses were reported.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] There have been no reports evaluating this agent in NPC or head and neck cancer, both of which are common among Chinese people, often relapse locally and are often resistant to radiotherapy and chemotherapy. In this study, the majority of subjects had been diagnosed with NPC or head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I/II trials have subsequently been conducted using AdV/TK/GCV in a number of malignant tumors, including ovarian carcinoma, brain tumors, prostate cancer, hepatocellular carcinoma and so on. [9][10][11][12][13][14] All of these trials have shown that the approach is relatively safe, but efficacy has been localized to the injection site, which has limited its use. However, this treatment may be particularly suitable for some tumors that have the tendency to relapse locally, such as head and neck cancer or nasopharyngeal carcinoma (NPC).…”
Section: Introductionmentioning
confidence: 99%